Buena administración para la efectividad de los Derechos Sociales - Lara Ortiz, María Lidón (Pontificia Universidad Católica del Perú, 2023)
The content and extension of the right to good administration is analyzed through a comparative study between the Ibero-American Charter of Rights and Duties of citizens regarding the Public Administration of 2013 and the Charter of Fundamental Rights of the European Union, especially in relation to the Spanish law, to determine the usefulness of good administration as a right of sub-rights that in addition to holding the status of independent right with its own autonomy, it serves as an instrument for the protection of other material rights of the citizen versus the public authorities, especially it happens regarding social rights.

Se analiza el contenido y extensión del derecho a la buena administración a través de un estudio comparado entre la Carta Iberoamericana de Derechos y Deberes de los ciudadanos ante la Administración Pública de 2013 y la Carta de Derechos Fundamentales de la Unión Europea, especialmente, en relación con el derecho español, para dirimir la utilidad de la buena administración como derecho de subderechos que, además de ostentar la condición de derecho independiente con autonomía propia, sirve como instrumento para la protección de otros derechos materiales del ciudadano frente a los poderes públicos, especialmente los derechos sociales.
Good administration for Social Rights effectiveness
Keywords: Social rights; Good administration; Transparency; Fundamental rights; Social responsibility of public administrations; Derechos sociales; Buena administración; Transparencia; Derechos fundamentales; Responsabilidad social de las Administraciones públicas; https://purl.org/pe-repo/ocde/ford#5.06.00